Dampak Game Online terhadap Pembelajaran Siswa di Sekolah Dasar - Aprianto, Irvandy; Dafit, Febrina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
In this digital era, it affects many aspects of life, especially developments related to online games. Starting from children, teenagers, and adults, almost everyone knows what an online game is. All of that certainly has a significant impact, especially for students still in the age of education and learning. This study aimed to determine the impact of online games on student learning at SDN 020 Langsat Hulu, Kuantan Singingi Regency. The method used in this research is the qualitative method. The research procedure is initial observation, problem formulation, research implementation, interviews and documentation, and data analysis. Data analysis using the concept of data analysis techniques Miles and Huberman. The results of this study are that online games have both positive and negative impacts. The negative impact is that children with high-intensity playing games impact lesson values ​​at school. In conclusion, online games in today's era have developed very quickly. Many elementary school children play online games themselves, so children become addicted to playing online games, making their children's learning disrupted because they play online games too often.